2015
DOI: 10.1016/j.clinthera.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Comanagement of Pediatric Depression and Obesity: A Clear Need for Evidence

Abstract: Purpose The purpose of this article is to provide a review of the existing literature for the comanagement of depression and obesity in the pediatric population. Methods A review of the current literature was conducted using EBSCOhost and EMBASE to identify evidence and recommendations for the comanagement of depression and obesity among children and adolescents (aged 2–18 years). Additional search criteria included peer-reviewed, English language–only full-text articles published before August 2015. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In this cross‐sectional study, we demonstrated that more than one‐third of overweight and obese children with elevated blood pressure had concurrent evidence of a MDO, a finding that is well above the overall lifetime prevalence of MDOs in US adolescents (14.3%) . While it is recognized that children with overweight/obesity suffer more from depression and anxiety that is multifactorial in etiology, what was particularly striking in our study was the finding that overweight/obese children with MDOs had 6.3 times greater odds of having hypertension than those without a MDO. Conversely, hypertensive children with overweight/obesity were 2.8 times more likely to have a MDO than normotensive children with overweight/obesity.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In this cross‐sectional study, we demonstrated that more than one‐third of overweight and obese children with elevated blood pressure had concurrent evidence of a MDO, a finding that is well above the overall lifetime prevalence of MDOs in US adolescents (14.3%) . While it is recognized that children with overweight/obesity suffer more from depression and anxiety that is multifactorial in etiology, what was particularly striking in our study was the finding that overweight/obese children with MDOs had 6.3 times greater odds of having hypertension than those without a MDO. Conversely, hypertensive children with overweight/obesity were 2.8 times more likely to have a MDO than normotensive children with overweight/obesity.…”
Section: Discussionsupporting
confidence: 45%
“…Several factors linking MDOs and CVD have been proposed, including unhealthy eating behaviors and macro‐/micro‐nutrient intake, demographic factors, and obesity . However, literature regarding the association of MDO with CVD risk factors and the comanagement of these conditions in youth is limited …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that priority should be given to correcting this deficiency. 6 The third article, by Mihalopoulos and Spigarelli, 7 reviews the disappointingly scarce literature on comorbid depression in obese adolescents. In many ways adolescents pharmacologically resemble adults more than they do children.…”
mentioning
confidence: 99%
“…Although one of our reviewers of this study felt that adult data for comorbid obesity and depression should have been relied on more for treatment of adolescents, in my view there are many reasons to suspect that adolescents could differ in their response to obesity, to its psychosocial effects, and, perhaps also, to its treatment. It is unfortunate that, as shown by Mihalopoulos and Spigarelli, 7 so little has been done to investigate these questions.…”
mentioning
confidence: 99%